Sociodemographic determinants of catch-up HPV vaccination completion between 2016-2019 in Norway. Issue 1 (31st January 2022) - Van Boetzelaer, E.; Daae, A.; Winje, B. A.; Vestrheim, D. F.; Steens, A.; Stefanoff, P.
ABSTRACT: Between 2016 and 2019, a catch-up human papillomavirus (HPV) vaccination took place in Norway for women born between 1991 and 1996. The aim of this study was to identify sociodemographic determinants of complete vaccination (3 doses) and partial vaccination (1–2 doses). A random sample of 10, 000 women who were offered catch-up HPV vaccination were invited. We assessed the association between sociodemographic characteristics and vaccination completion using univariable and multivariable multinomial logistic regression. Of 4, 967 respondents, 3, 464 (63%) received complete vaccination and 298 (7%) received partial vaccination. 30% did not receive any vaccination and functioned as reference group. Compared with having Norwegian caregivers, having a caregiver from non-western countries decreased the odds of partial and complete vaccination (aOR = 0.57; 95%CI = 0.35–0.95 and aOR = 0.57; 95%CI = 0.44–0.74). Having a caregiver from other western countries decreased the odds of complete vaccination (aOR = 0.72; 95%CI = 0.52–0.98). Residing in Norway for 10 years or longer significantly increased the odds of complete vaccination (aOR = 2.65; 95%CI = 1.58–4.43). Being in a relationship significantly increased the odds of partial vaccination compared with being single (aOR = 1.50; 95%CI = 1.02–2.21). Being married (aOR = 0.66; 95%CI = 0.50–0.86) and having children (aOR = 0.53; 95%CI = 0.42–0.68) decreased the odds of complete vaccination. Having university education increased the odds of both partial and complete vaccination (aOR = 2.19; 95%CI = 1.47–3.25 and aOR = 4.11; 95%CI = 3.33–5.06). Having a caregiver born outside of Norway, having children and being married decreased the odds of receiving complete HPV vaccination. This highlights the need to target communication around HPV vaccination toward different ethnic communities and include more specific messaging that having children and being married does not necessarily prevent HPV infections.